Addiction and depression comorbidity approaches - Crnić Katarina A.B; Todorović Mirjana M.; Marković Srđan Z.; Kastratović Dragana A.; Timotijević Ivana P. (Srpsko lekarsko drustvo, 2016)
Topic: Comorbidities, simultaneous occurrence of two or more disorders are common in psychiatry; therefore the concept of dual diagnosis was established due to new ethiopatogenetic dilemmas and principles of diagnosis and treatment of these conditions. The most common are comorbid affective disorders and comorbidity of drug addictions and affective disorders. Topic position in medical public: Epidemiological studies show a high percentage of comorbidity of drug addictions and depression. Various studies show that about one-third of individuals with depression have addiction, and often some other psychiatric disorders are present, such as personality disorder, anxiety, and bipolar affective disorder. Comorbid disorders exacerbate one another; have tendencies to chronicity and treatment resistance. The problem of adequate diagnosis is common; other diagnosis is neglected, leading to inadequate treatment and poor outcomes. Researches of possible causes of addiction and depression comorbidity follow different theoretical assumptions. One favor genetically determined vulnerability, the others are addressing to the impact of trauma in the formative stages of personality development. Widespread is the theoretical assumption on the deficit functioning of the same regions of the CNS and the same neurotransmitters system. In previous studies the preclinical ones dominate, which are theoretically placed in the context of the CNS of a man. Most of the research are related to dysfunction of the serotonergic and dopaminergic systems, whose influence on addiction and depression are clear, and recent studies show the importance of neuromodulators and their receptors, for example, the role of natural opioid dynorphin and 'kappa' receptors in the mesolimbic reward system. Further action: The better diagnosis would require proper screening of patients entering addiction treatments for affective disorders and vice versa. Treatment have to be combined; in addition to medications for addiction essential are antidepressants, atypical antipsychotics, and/or mood stabilizers, for better therapeutic results.